Algorithms and Models for the Web Graph 8th International Workshop, WAW 2011, Atlanta, GA, USA, May 27-29, 2011. Proceedings - Frieze, Alan.; Horn, Paul.; Pralat, Pawel; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 8th International Workshop on Algorithms and Models for the Web-Graph, WAW 2011, held in Atlanta, GA, in May 2011 - co-located with RSA 2011, the 15th International Conference on Random Structures and Algorithms. The 13 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from 19 submissions. Addressing a wide variety of topics related to the study of the Web-graph such as theoretical and empirical analysis, the papers feature original research in terms of algorithmic and mathematical analysis in all areas pertaining to the World-Wide Web with special focus to the view of complex data as networks.
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Computer software; Computational complexity; Data mining; Information storage and retrieval systems; Information systems; Electronic books